Augmented Reality dalam Pembelajaran Tata Busana : Kajian Literatur tentang Visualisasi Materi Pembelajaran, Hasil Belajar, dan Kompetensi Praktik (Lembaga Pengembangan Kinerja Dosen, 2026)
Fashion education requires media capable of visualizing abstract, procedural, and skill-based materials. This study analyzes the use of Augmented Reality (AR) in fashion education, focusing on material visualization, learning outcomes, and practical competencies. A systematic literature review was conducted on publications from 2020–2026 retrieved from Google Scholar, Scopus, ScienceDirect, ERIC, SpringerLink, and Garuda. Data were analyzed through content analysis and thematic synthesis. The results show that AR is implemented through e-books, smartphone applications, and flash cards integrating QR codes, three-dimensional objects, audio, quizzes, and 360-degree rotation. These features support learners’ understanding of garment components, pattern construction, and practical procedures while promoting independent learning. AR-based media generally demonstrate positive tendencies toward motivation, conceptual understanding, learning outcomes, and practical competencies. However, implementation is influenced by device compatibility, internet access, teachers’ digital literacy, media quality, and institutional support. AR can connect theoretical understanding with practical skills when designed according to learning objectives, curriculum requirements, and technological readiness.